Biaxial/Multiaxial fatigue and fracture - International Conference on Biaxial/Multiaxial Fatigue and Fracture 2001 : Lisbon, Portugal); Carpinteri, Andrea; Freitas, Manuel de.; Spagnoli, Andrea; European Structural Integrity Society (Amsterdam ; Oxford : Elsevier, 2003)
The European Structural Integrity Society (ESIS) Technical committee on Fatigue of Engineering Materials and Structures (TC3) decided to compile a Special Technical Publication (ESIS STP) based on the 115 papers presented at the 6th International Conference on Biaxial/Multiaxial Fatigue and Fracture. The 25 papers included in the STP have been extended and revised by the authors. The conference was held in Lisbon, Portugal, on 25-28 June 2001, and was chaired by Manual De Freitas, Instituto Superior Tecnico, Lisbon. The meeting, organised by the Instituto Superior Tecnico and sponsored by the Portuguese Minesterio da Cienca e da Tecnologia and by the European Structural Integrity Society, was attended by 151 delegates from 20 countries. The papers in the present book deal with the theoretical, numerical and experimental aspects of the Multiaxial fatigue and fracture of engineering materials and structures. They are divided in to the following six sections; Multiaxial Fatigue of Welded Structures; High cycle Multiaxial fatigue; Non proportional and Variable-Amplitude loading; Defects, Notches, Crack Growth; Low Cycle Multiaxial Fatigue; Applications and Testing Methods. As is well-known, most engineering components and structures in the mechanical, aerospace, power generation, and other industries are subjected to multiaxial loading during their service life. One of the most difficult tasks in design against fatigue and fracture is to translate the information gathered from uniaxial fatigue and fracture tests on engineering materials into applications involving complex states of cyclic stress-strain conditions. This book is the result of co-operation between many researchers from different laboratories, universities and industries in a number of countries.
Multiaxial fatigue of welded structures, High cycle multiaxial fatigue, Non-proportional and variable-amplitude loading, Defects, notches, crack growth, Low cycle multiaxial fatigue, Applications and testing methods.
"This volume contains 25 peer-reviewed papers selected from those presented at the 6th International Conference on Biaxial/Multiaxial Fatigue and Fracture held in Lisbon, Portugal, 25-28 June 2001."
Includes bibliographical references and index.
Keywords: Materials -- Fatigue -- Congresses; Electronic books; Conference proceedings